1357 Patient-reported outcome measure for older people living with frailty receiving acute care (PROM-OPAC): a programme of development and field-testing. Issue 12 (22nd November 2022) - Oppen, James van; Coats, Timothy; Conroy, Simon; Valderas, Jose M; Mackintosh, Nicola
Abstract : Aims, Objectives and Background: Acute healthcare outcomes for older people living with frailty are not meaningfully measured using only service delivery metrics (time targets) or broad outcomes (mortality). This programme developed and field-tested a novel Patient Reported Outcome Measure (PROM). Method and Design: 1: To define important healthcare goals, interviews were conducted with older people living with frailty during acute care. 2: A systematic review searched for measures previously used for older people with frailty in acute settings. These measures were appraised for content validity with lay collaborators and patient participants. 3: Some areas identified in [1] had no existing measures, so novel questions were devised, improved, and reduced using co-creation and cognitive interviews with lay collaborators and patient participants. 4: The resulting questions were field-tested for feasibility and psychometric performance with a multi-site cohort of patients. Results and Conclusion: 1: Acute healthcare outcome goals were classified under Autonomy (information, security, control) and Function (physical, psychosocial, symptom relief). 2: Four existing sets of questions measuring Function were identified. EQ-5D provided the best compromise between reliability and burden. 3: There were no existing measures of Autonomy, so seven novel questions were developed and scaled. 4: When Function and Autonomy questions were tested in 128 patients, median completion time was 12 minutes and most participants required researcher assistance. Mean inter-item correlation for novel items was 0.28 with adequate response distribution. Exploratory factor analysis ( Table 1 ) indicated a three-factor structure (RMSEA, 0.043) with good internal consistency (Cronbach's alpha, 0.73. Range for subscales, 0.62–0.77). 35% returned a post-discharge retest. Summary: From patient interviews, the PROM-OPAC was developed to measure Autonomy (seven novel questions) and Function (EQ5D). In-hospital and follow-up collection appeared feasible, although users required support to overcome accessibility barriers. Validation in multi-site cohorts is ongoing. Potential future applications include system-level metrics, service-level quality improvement, and patient-level shared decision-making.